Effects of defoliation frequency and intensity on production of four burned and unburned bushed grassland communities in south Central Kenya. - Too, D.T. (Texas A&M University, 1985)
Effects of defoliation frequency and intensity on production of burned and unburned plant communities were studied in Kenya on the National Range Research Station, Kiboko in 1982-1983. Study sites were located in ecological zone V which showed some contrast in topography, soils and dominant grasses. Two replications of four plant communities, dominated by combinations of five grasses were included within eight explosures. Grass was clipped from two to seven times a year to estimate seasonal and cumulative biomass yield under two clipping intensities and a dry season burn. The four plant communities were not statistically different (P.0.05). However, community variation existed with the Digitaria community yielding the most phytomass and Digitaria-Themeda the least. Fire had no significant effect on overall yields of grassland communities. However, significant treatment effect was noted especially on burned plots. Treatment 1, which was clipped the most (13 times) during the study period had the most phytomass compared to all other treatments. Treatment 4 which was defoliated 5 times had the lowest phytomass. Intensity of clipping did not show any significant differences. Phytomass from the heavy defoliation intensity (5 cm) was slightly higher than the moderate (12.5 cm) intensity. Soil physical characteristics had marked influence on species composition and had moderate influence on production. Clay loams had more biomass production than sandy soils. Soils with high organic matter content had more phytomass than those with low organic matter. Sites with longer wet periods had more production than those which dried soon after the rains.